(untitled) (Jurnal Pembangunan Sosial, 2013)
This study is an attempt to identify the relationship between housing space environment and adolescence misconduct, such as crime and aggression in a low cost housing area. The objective of the study is to identify the satisfaction towards physical and environment of low cost housing and its relationship with adolescence misconduct. A total of 333 sub-sample of parent’s and 333 sub-sample of adolescence had been randomly as study samples Result showed that there was no significant relationship between the physical and environment housing space with the adolescence misconduct (p>0.01). There was also no significant difference of the physical and environment housing space based on the parent’s ethnicity (p>0.01). Therefore, the physical and environment housing space had no significant impact on the adolescence misconduct.